Delayed coronary obstruction leading to death following balloon dilation in self-expanding aortic valve for acute coronary occlusion: a case report - Haoran Zhang; Donghui Zhang (Frontiers in Cardiovascular Medicine)
BackgroundFollowing transcatheter aortic valve replacement, acute coronary obstruction is infrequent but potentially life-threatening, while delayed coronary obstruction is even more uncommon.Case summaryA 69-year-old male underwent TAVR and subsequently developed an acute obstruction in the left main coronary artery. Interventional management involved performing percutaneous transluminal coronary angioplasty using balloon dilation on both the left main coronary artery and its ostium. Intravascular ultrasound confirmed successful dilation of the coronary ostium. The patient experienced resolution of symptoms, and ventricular premature beats disappeared on electrocardiogram monitoring. However, the patient unfortunately succumbed to sudden death one month after discharge.ConclusionGuidewires for chronic total occlusion may be necessary for patients with severely calcified and stenotic aortic valves that are challenging to navigate. Before undertaking TAVR, precise preoperative evaluation, including accurate risk assessment, multimodal imaging, and thorough planning, is essential. While balloon dilation can provide temporary relief for coronary obstruction, it carries the risk of subsequent delayed coronary occlusion with serious consequences. Chest pain experienced under local anesthesia more directly suggests coronary occlusion.